Kommunikationsapplikation för konsultföretag - Jupiter, Alice; Kinfe, Yodit (My University, 2020)
This project is based on a current user need that exists at a consulting company, Technity AB, operating in the Gothenburg region, whose business conducts both customer and in-house projects. The services the company offers occasionally entails that the staff gets stationed at customer offices. Thus, the location of the company’s coworkers is scattered, which influences the internal communication of the company negatively. Inadequate communication within businesses could entail for instance inefficiency, deteriorating working relationships, reduced experienced business affiliation and mental illness, whereupon the current need of a service that eliminates the problem situation exists. The result from this thesis has the goal to fulfil the need, demands and expectations which are projected onto the product, whose purpose is to aid the company’s communicative and informative flows. The proposed solution should therefore obtain a result with a standard high enough to be able to be used as a basis for implementation at the company. The process towards the project goal follows the general work process in the interaction design methodology, which includes: problem research, concept generation, concept selection, prototyping and usability testing as well as implementation, which are adapted accordingly to the conditions of the project. During the course of the process participants from the target group are included numerous times in order to obtain a user-centered product development. The result is a composition of two final concepts that has means of information sharing and communication. The end product is a mobile application specifically intended for use by consulting companies where users have the opportunity to share news, personal posts, company information, staffing resources and, finally, direct messages both individually and in a group.
Keywords: consultant, interaction design, mobile application, communication